DIGITALIZATION AS A MODERN CONDITION OF SOCIAL INTERACTION IN CULTURE - Lyudmila S. Gasparyan (Russian Studies in Culture and Society)
The formation of the digital environment leads to the development of new behaviors, where the principle of social interaction is fundamentally changing. Obviously, these changes will be one of the most significant aspects of shaping the world picture. The emerging difference in the ways of interaction actualizes research in the field of constructing a social reality that acquires a predetermined meaning and shape, within which technological aspects become much more significant than substantive ones.